Research on an Intelligent Design Method for the Geometric Structure of Three-Layer Hollow Fan Blades - Jialin Lei; Jiale Chao; Chuipin Kong; Xionghui Zhou (Aerospace)
The geometric structure design of three-layer hollow fan blades is extremely complex, which is not only directly related to the blade quality and manufacturing cost but also has a significant impact on engine performance. Based on geometric algorithms and combined with design rules and process constraints, an intelligent design method for the geometric structure of three-layer hollow blades is proposed: A new cross-section curve design method based on a non-equidistant offset is presented to enable the rapid design of wall plate structure. An innovative parametric design method for the corrugation structure in cross-sections driven by process constraints such as diffusion bonding angle thresholds is put forward. The spanwise rib smoothing optimization is realized based on the minimum energy method with the corrugation angle change term. The cross-section densification design is carried out to improve the accuracy of wireframe structure and achieve the rapid solid modeling of hollow blades. Finally, the proposed methods are seamlessly integrated into the NX software (version 12), and a three-layer hollow fan blade intelligent design system is developed, which enables the automated design and modeling of the complex geometric structure of the hollow blade under an aerodynamic shape and a large number of design and process constraints.